2012
DOI: 10.1111/j.1556-4029.2012.02277.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Colonization Behavior of Blowflies (Diptera: Calliphoridae) in Southeastern Australia

Abstract: Worldwide research into nocturnal colonization by blowflies has produced many contradictory findings, prompting investigation specific to southeastern Australia. Initial experiments showed that blowfly colonization begins shortly after sunrise and continues until sunset; nocturnal colonization never occurred. Colonization peaks occurred at mid-morning, midday, and in the hours preceding sunset. In an additional experiment, wild blowflies were captured and placed in cages with colonization medium supplied noctu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…Nocturnal oviposition was not detected in this study, in line with previous report in the United States . In Australia, George et al did not detect oviposition at night in the field, but limited colonization of substrates occurred under artificial conditions. Absence of nocturnal oviposition was described in Germany by Amendt et al , who reported limited egg‐laying behavior for L. sericata in the absence of light—in only two of 57 caged baits.…”
Section: Discussionsupporting
confidence: 91%
“…Nocturnal oviposition was not detected in this study, in line with previous report in the United States . In Australia, George et al did not detect oviposition at night in the field, but limited colonization of substrates occurred under artificial conditions. Absence of nocturnal oviposition was described in Germany by Amendt et al , who reported limited egg‐laying behavior for L. sericata in the absence of light—in only two of 57 caged baits.…”
Section: Discussionsupporting
confidence: 91%
“…No nocturnal blow fly activity or oviposition was recorded during any of the 25 nocturnal sampling periods conducted in 2011 and 2013. These results support the theory that blow flies do not visit bait to oviposit during the hours of complete darkness .…”
Section: Discussionsupporting
confidence: 86%
“…To date, there is variability in the published literature relating to nocturnal activity and oviposition behavior. While some studies support the observation that oviposition does not occur at night (1)(2)(3)(4)(5)(6)(7), others have found clear evidence that it is possible (8)(9)(10)(11)(12)(13)(14). Laboratory work conducted to investigate conditions facilitating nocturnal oviposition has also proved inconclusive.…”
mentioning
confidence: 99%
“…It is possible that these females possessed copies of mutated circadian genes as observed in D. melanogaster . Variable numbers of arrhythmic females in local populations may actually be responsible for the conflicting results seen in studies of nocturnal colonization globally warranting further research in this area.…”
Section: Discussionmentioning
confidence: 99%
“…This may be an important consideration in forensic entomology cases where death has occurred at night, and the entomologist is asked to calculate a minimum postmortem interval. Many studies show conflicting results about the existence of nocturnal oviposition in different geographical regions, or arising from different study designs, even when the same species are involved (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Making sense of this variation therefore requires investigation of the diel patterns that underlie oviposition, both at a behavioral and a molecular level.…”
Section: Insect Rhythmsmentioning
confidence: 99%